Efficacy and safety of PARP inhibitors in advanced or recurrent endometrial cancer: a systematic review and meta-analysis - Zhang, Huanhuan; Yan, Guangwei; Yan, Jinxiang; Zeng, Xianxu (Frontiers in Immunology, 2026)
ObjectiveSeveral clinical trials have explored the efficacy and safety of Poly (ADP-ribose) polymerase (PARP) inhibitors in endometrial cancer (EC). However, evidence supporting PARP inhibitors alone or in combination with other medications in advanced or recurrent EC remains limited.MethodsWe utilized Cochrane Library, PubMed, Web of Science, and Embase to identify clinical trials that evaluated the efficacy and safety of PARP inhibitors in advanced and recurrent EC. The outcomes analyzed included progression-free survival (PFS), overall survival (OS), objective response rate (ORR), and adverse events (AEs). We computed hazard ratios (HRs) for PFS and OS, with 95% confidence intervals (CIs) from randomized trials. Subgroup analysis was conducted based on the PARP inhibitor combination therapy strategies (with antiprogrammed death 1 [PD-1]/antiprogrammed death ligand-1 [PD-L1] inhibitors or antiangiogenic agents).ResultsOverall, 12 clinical trials for a total number of 1,594 patients diagnosed with advanced or recurrent EC were included in this meta-analysis. The duration of follow-up time ranged from a median of 7.4 to 31.9 months, and the pooled median PFS was 6.43 months. The results showed that the combination of PARP with PD-L1/PD-1 inhibitors could significantly prolong PFS versus placebo (hazard ratio [HR] = 0.567; 95% confidence interval [CI] = 0.469–0.686; p < 0.05). Based on the subgroup analysis, the pooled median PFS was found to be 7.59 months for the combination of PARP with PD-L1/PD-1 inhibitors. In addition, the pooled median PFS at 6 months was 0.44 based on the analysis of four included studies. In the intention-to-treat population, there was no PFS/OS difference between PARP inhibitor monotherapy and placebo (PFS: HR = 0.684 [95% CI = 0.334–1.398], p > 0.05; OS: HR = 0.787 [95% CI = 0.279–2.219], p > 0.05). The ORR was notably elevated in the combined therapy group compared with PARP inhibitor monotherapy (OR = 3.34 [95% CI = 1.095–10.165], p = 0.034). The most common AEs included fatigue (226, 54.5%), nausea (219, 52.8%), anemia (219, 52.8%), diarrhea (127, 30.6%), and alopecia (121, 29.2%).ConclusionThe combination of a PARP inhibitor with a PD-L1/PD-1 inhibitor shows modest activity with substantial toxicity, particularly in heavily pretreated and largely pMMR populations.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024556356.